Pengaruh Kombinasi Fe dan Pisang Ambon terhadap Kadar Hemoglobin Ibu Hamil Anemia di Klinik Dafa Husada Malang - Sumbawati, Reshinta Dwi; Alfitri, Rosyidah (Mando Care Jurnal, 2025)
Background: Efforts to increase Hb levels by consuming Ambon bananas, which contain vitamin C, vitamin B6, and iron, can help stimulate hemoglobin production in the blood of people with anemia. Objective: This study aimed to determine the effect of the combination of Fe and Ambon bananas on hemoglobin levels in anemic pregnant women. Method: A quasi-experimental pretest–posttest design with a control group. The study was conducted at the Dafa Husada Clinic in Malang. The sampling technique used purposive sampling. A total of 15 pregnant women with anemia were sampled, divided into two groups: the experimental group and the control group. Data analysis used paired t-tests and independent samples t-tests. Results: The average Hb level in the experimental group before being given Ambon bananas was 10.687 g/dL, and after being given Ambon bananas, it was 12.313 g/dL. Meanwhile, in the control group, before the intervention, it was 10.720 g/dL, and after being given Fe tablets alone, it was 11.648 g/dL. The independent t-test showed a p-value of 0.000 < 0.05. The combination of Fe and Ambon bananas significantly affected hemoglobin levels in anemic pregnant women, and there was a difference in hemoglobin levels between the experimental and control groups after the intervention. Recommendation: Pregnant women should increase their knowledge about how to increase hemoglobin levels so they can manage anemia independently by regularly consuming Ambon bananas